Oral squamous cell carcinoma: status of tight junction claudins in the different histopathological patterns and relationship with clinical parameters. A tissue-microarray-based study of 136 cases. Issue 7 (30th June 2010) - Lourenço, Silvia V; Coutinho-Camillo, Cláudia M; Buim, Marcilei E C; Pereira, Cláudia M; Carvalho, André L; Kowalski, Luiz P; Soares, Fernando A
Abstract : Aims: Claudins are integral transmembrane proteins of the tight junctions, critical for maintaining cell adhesion and polarity. Alterations in the expression of individual claudins have been detected in carcinomas and appear to correlate with tumour progression. Methods: In this study, a panel of anti-claudin antibodies (anti-claudins 1, 2, 3, 4, 5 and 7) was employed to map claudin expression in 136 cases of oral squamous cell carcinoma (OSCC) organised in a tissue microarray. Results: Claudins were expressed in a reticular pattern up to the prickle layer in normal mucosal epithelium. In OSCC, claudins were strongly present in well-differentiated tumours, they presented mild and low expression in moderately differentiated OSCC, and were negative in poorly differentiated OSCC; the absences of claudin 1 (p=0.002) and claudin 4 (p<0.001) were associated with moderately/poorly differentiated tumours. Strong expression of claudin 4 was associated with decreased perineural infiltration (p=0.024). Claudins 5 and 7 were mostly negative or weakly expressed in all cases studied. Expression of claudin 7 was associated with the early clinical stages of the disease, whereas loss of claudin 7 tended to be more frequent in advanced stages of OSCC (p=0.054). Absence of claudin 7 was also associated with absent vascular infiltration (p=0.045) and with presence of recurrence (p=0.052). Conclusions: Claudin expression patterns showed a strong correlation with histological type of OSCC; claudin expression was decreased in areas of invasion, and negative in poorly differentiated tumours. This pattern may be related to evolution and prognosis of these tumours, especially in the case of claudin 7, which seems to be associated with a poor prognosis in OSCC.